ESG impact on performance of US S&P 500-listed firms - Alareeni, Bahaaeddin Ahmed; Hamdan, Allam (Corporate governance (Bradford), 2020)
Purpose This paper aims to investigate whether there are relationships among corporate disclosure of environmental, social and governance (ESG) and firms’ operational (ROA), financial (ROE) and market performance (Tobin’s Q), and if these relationships are positives or negatives or even neutral. Design/methodology/approach The study sample covers US S&P 500-listed companies during the period 2009 to 2018. Panel regression analysis was used to examine the study hypotheses and achieve the study aims. Findings The results showed that ESG disclosure positively affects a firms’ performance measures. However, measuring ESG sub-components separately showed that environmental (EVN) and corporate social responsibility (CSR) disclosure is negatively associated with ROA and ROE. EVN and CSR disclosure is positively related to Tobin’s Q. Further, corporate governance (CG) disclosure is positively related to ROA and Tobin’s Q, and negatively related to ROE. More importantly, ESG, CSR, EVN and CG tend to be higher with firms that have high assets and high financial leverage. Furthermore, the higher level of ESG, EVN, CSR and CG disclosure, the higher the ROA and ROE. Originality/value The study limns a vision of the role of ESG on firm performance. This study tries to determine whether there are relationships among all ESG disclosure and FP, and if they are positive, negative or even neutral.